What is a football champion made of? Scoring and preventing opponent teams from scoring in the 21st century in the top six European leagues - Matos, Rui (2023)
The present study aimed to compare the scored and conceded goals of the top six European football leagues (Portugal, Spain, France, Italy, England, and Germany) between 2001 and 2020. The champions have a mean combo (indicator that combines attack and defence ranking) result between 1 and 1.40. The French and Italian leagues were the only ones where variation coefficients of this combo result overpassed 50% (71 and 59%, respectively) compared to the remaining football leagues. Further subsequent analysis showed that the Portuguese and French leagues differ significantly from Italy in terms of the best attack position of the champions (Z= 3.196; p= 0.01; η2= 0.123). Regarding position in the defensive ranking, Portugal and Italy showed significantly different results compared to France (Z= 3.763; p= 0.003; η2= 1.42). Besides, the only two countries with significant differences in scored and conceded goals positioning were France (attack better than defence; t= -3; p< 0.01; d= 2.236) and Italy (defence better than attack; t= 2.881 p< 0.01; d= 1.164). Hence, in the French football league, a higher attack performance than a defence seems to indicate the champion. Oppositely, in the Italian football league, champions traditionally occupy top positioning on defence, even if they do not present the same performance on scored goals.